Youngsuk Chae (2015) Postcolonial ecofeminism in Arundhati Roy’s The God of Small Things, (Journal of Postcolonial Writing, 2015)
This article foregrounds Arundhati Roy’s postcolonial ecofeminist perspective in her novel The God of Small Things (1997). Roy has become recognized as an environmental and political activist through her criticism of postcolonial India’s mal- development. Although she is cynical about state-sponsored development projects, her criticism is focused not on the idea of development per se, but on the hierarchy of dualisms that legitimizes the exploitation of nature by the human, of women by men and of the oppressed by the powerful. The God of Small Things interrogates the ways such hierarchies operate through mechanisms such as patriarchical ideology and an apparently rational economic logic. Roy’s critique of environmental exploitation in postcolonial India reveals the interconnectedness of ecological deterioration and oppression based on gender, class and race. Such exploitation calls for an examination of postcolonial environment issues from an ecofeminist viewpoint. The convergence of postcolonialism with ecofeminism – what is here called postcolonial ecofeminism – is exemplified in Roy’s novel